The origin of nausea in migraine–A PET study - Maniyar, Farooq H (J Headache Pain, 2014)
BACKGROUND: Nausea is a common and disabling symptom of migraine. The origin of nausea is not well understood although functional connections between trigeminal neurons and the nucleus tractus solitarius may explain occurrence of nausea with pain. However, nausea occurs as a premonitory symptom in about a quarter of patients, suggesting that a primary brain alteration unrelated to the experience of pain may be the reason for nausea. METHODS: We performed positron emission tomography scans with H(2)(15)O PET in premonitory phase of nitroglycerin-induced migraine and compared patients with and without nausea. RESULTS: The results showed activation in rostral dorsal medulla and periaqueductal grey (PAG) in the nausea group, which was absent in the no nausea group. The rostral dorsal medullary area included the nucleus tractus solitarius, dorsal motor nucleus of the vagus nerve and the nucleus ambiguus, all of which are thought to be involved in brain circuits mediating nausea. CONCLUSIONS: The results demonstrate that nausea can occur as a premonitory symptom in migraine, independent of pain and trigeminal activation. This is associated with activation of brain structures known to be involved in nausea. We conclude that nausea is a centrally driven symptom in migraine.